Todos os caminhos levam à Geledés: narrativas de autonomia através da organização de mulheres Negras em São Paulo - Prado, Suelen Girotte do (2020)
Brazilian black women, as part of the peoples of the black diaspora, represent fundamental figures in the historical trajectory of resistance and the elaboration of strategies for the existence and survival of black communities. What we know as black feminism has its genesis in this journey, and in these reframing processes in which organized black women, since the 1970s, as a social movement, placed their demands and the consequences that fell on their condition as a social subject. In this context, the trajectory of the black women founders of the Geledés Institute is inserted as an important part of the process that led, in 1988, to the foundation of this non-governmental organization, which through the collective initiative, of the Programs developed as work strategies, positioned themselves and engendered actions in order to subsidize the demands of inequality to which the black population and especially black women were exposed. We then proposed, through this dissertation, to identify and analyze, the organization of the agenda of Black Women’s Movement founders of Geledés, in the 1980s and 1990s. Through our sources, which included depositions provided by four interviewees, we developed our work, in order to understand, based on the Institute’s practices, how the actions of this entity took place, which contributed to the political location for the agenda of political minorities and also producing a set of knowledge through a collective process